Legalidad flexible y discrecionalidad judicial en el sistema italiano de la responsabilidad penal de las personas jurídicas - Mongillo, Vincenzo (2025)
The essay analyzes the role of discretion within the system of corporate liability established in Italy by Legislative Decree No. 231/2001, highlighting the flexibility of the constitutive elements of the “corporate” offense arising from the commission of crimes, the persistent uncertainties regarding the assessment of organizational defects, and the breadth of judicial power in determining corporate sanctions. It underscores how a proper channeling of discretion—guided by the normative telos and, in particular, by the aims of ex ante prevention and ex post reparation—can help strengthen the effectiveness and rationality of the system, reducing the risks of arbitrariness and excessive unpredictability in judicial decisions. The paper concludes by identifying possible avenues for reform aimed at consolidating normative determination and achieving a balance between efficiency requirements and safeguards.